Beyond flexibility: controlling stem cells in an ever changing environment - Pfeiffer, Anne; Wenzl, Christian; Lohmann, Jan U. (Current opinion in plant biology, 2017)
Developmental plasticity is a defining feature of plants allowing them to colonize a wide range of different ecosystems by promoting environmental adaptation. Their postembryonic development requires life-long maintenance of stem cells, which are embedded into specialized tissues, called meristems. The shoot apical meristem gives rise to all above ground tissues and is a complex and dynamic three-dimensional structure harboring cells of different clonal origins and fates. Functionally divergent subdomains are stably maintained despite permanent cell division, however their relative sizes are modified in response to developmental and environmental signals. In this review, we briefly describe the core regulatory program of the shoot apical meristem and discuss progress in the fields of mechanical and environmental control of its activity.